Morphologic features in cystic lesions of pancreas-a retrospective analysis - P. J., Cicy; Gopinathan, Jeji; P, Lekshmi Devi; Ulahannan, Sansho Elavumkal (International Journal of Advances in Medicine, 2018)
Background: Cystic lesions of pancreas consist of a broad spectrum of reactive, benign and malignant conditions. The most common among cystic pancreatic lesions is pseudocyst of pancreas. Cystic tumours of pancreas are less common than solid one’s accounting for less than 1% according to some studies. Literature review showed only a few extensive studies on cystic lesions of pancreas, especially from South India. Methods: Our research is a descriptive histopathological analysis of 38 cases of cystic lesions of pancreas, done in the department of pathology of our institution, over a period of 5 years. Results: We received a total of 38 cases of cystic lesions of pancreas. The age distribution ranged from 17 to 77 years. Male to female ratio was 24: 14. There were neoplastic and non neoplastic entities. Pseudocyst of pancreas was the most common cystic lesion (12 cases). Benign neoplasms included serous cystadenomas, mucinous cystadenomas and lymphangiomas. Ductal adenocarcinomas with cystic degeneration and adenocarcinomas with mucinous component were some of the malignant cystic lesions. Conclusions: Cystic pancreatic lesions accounted for 24% of all the pancreatic lesions received in our institution during the period of this study. 24 cases (63%) were benign lesions and 14 cases (37 %) were malignant. Though cystic lesions of pancreas especially neoplasms are less frequent than solid neoplasms, it is important to study their diagnostic features since the management differs. Imaging studies may be similar in some cystic lesions. A proper clinicoradiological correlation and detailed investigational work up will aid in the correct diagnosis.